Keeping phase III tuberculosis trials relevant: Adapting to a rapidly changing landscape. - Patrick P J Phillips; Carole D Mitnick; James D Neaton; Payam Nahid; Christian Lienhardt; Andrew J Nunn (PLoS Medicine)
In a Collection Review, Patrick Phillips and colleagues discuss developments in clinical trial design for the evaluation of TB therapeutics.